Oil Height Determination From Capacitance Tomography Measurements Using Neural Network. - Mohamad-Saleh, J; Abdul-Salam, R. (2004)

(untitled)
This paper presents a "direct" method to gas-oil interface level determination using an artificial neural network approach based on Electrical Capacitance Tomography (ECT) measurements. "Direct" here means that the gas-oil interface levels are obtained directly from the ECT measurements without recourse to image reconstruction. The preliminary work models a separation tank that is filled with gas and oil.